EVALUASI KINERJA KEPALA SEKOLAH MENENGAH KEJURUAN NEGERI DI KOTA BANDAR LAMPUNG - Yetri, Yetri (UIN Alauddin Makassar, 2015)
Abstract: The objective of this research was to determine the suitability of the principalsâ performance in carrying out managerial tasks with the established standards, including performance in: (1) leading the school in the context of the utilization of school resources optimally, (2) managing changes and development of the school towards an effective learning organization, (3) creating a culture and school climate which are conducive and innovative, and (4) utilizing the advancement of ICT in learning and school management. The approach and evaluation model chosen in this study was a goal-based evaluation model which was combined with evaluation model that were generally developed in several government institutions. The research method was qualitative. The data were collected by using observation, interview, and documents. The results of the research showed that: (1) the performance of the principals in leading the school were in good category, (2) the performance of the principals in managing change and school development were in good category, (3) the performance of the principal in creating a culture and school climate were in good category, and (4) the performance of the principal in the use of ICT in teaching and school management were in enough category. The conclusion of the research was, of the four aspects of the performance of principals evaluated, three of them showed the achievement of performance was good category, and one aspect was in enough category. However, in each aspect in the evaluation there were still some performance criteria that have not been achieved well, or there were still in the enough category.Abstrak: Tujuan penelitian ini adalah untuk mengetahui kesesuaian antara prinsip-prinsip kinerja yang digunakan dalam menunaikan tugas managerial dengan standar kinerja yang telah ditetapkan, meliputi: (1) upaya memajukan sekolah dalam konteks pemanfaatan sumber-sumber sekolah secara optimal; (2) mengelola perubahan-perubahan dan pengembangan sekolah menuju organisasi belajar yang efektif; (3) menciptakan budaya dan suasana sekolah yang kondusif dan inovatif; (4) penggunaan ICT dalam pembelajaran dan manajemen sekolah. Penelitian menggunakan pendekatan evaluasi sebagai dengan model goal based yang secara umum dikembangkan sebagai model mengevaluasi lembaga-lembaga pemerintahan. Penelitian menggunakan metode kualitatif. Data dikumpulkan dengan menggunakan observasi, wawancara dan dokumentasi. Hasilnya menunjukkan: (1) kinerja kepemimpinan di sekolah sudah dalam kategori baik, (2) prinsip-prinsip kinerja dalam mengelola perubahan dan pengembangan sekolah dalam kategori baik, (3) prinsip-prinsip kinerja dalam menciptakan budaya dan suasana sekolah dalam kategori baik, (4) prinsip-prinsip kinerja dalam menggunakan ICT pembelajaran serta pengelolaan sekolah dalam kategori baik. Kesimpulannya adalah, dari empat aspek prinsip kinerja yang dievaluasi, tiga diantaranya dalam kategori baik dan satu diantaranya kategori cukup.